Potensi Stabilisasi Membran Sel dari Ekstrak Berbeda Kepolaran Sirih Bumi (Peperomia pellucida [L.] Kunth) sebagai Agen Antiinflamasi - Ayu Kartika, I Gusti Agung; Suryani, Suryani; Setya Palupi, Dwi Hadi; Adnyana, I Ketut (Faculty of Pharmacy, Universitas Pancasila, 2023)
Sirih bumi (Peperomia pellucida [L.] Kunth.) is a medicinal herb. Anti-inflammatory activities are reported. These plant extracts have been shown to reduce inflammation in many studies, but it is unknown which extract works best. The objectives if this study were determine the extract that has the best anti-inflammatory activity from sirih bumi. The activity was assessed from the impact of stabilising red blood cell membranes in vitro. The research was then continued with a literature study on the chemical compounds containing the best extracts. To determine the prediction of the compound responsible for its activity and potency, several in silico tests were carried out, such as PASS online, Pre-ADMET online, and Protox II. The test results showed that the ethyl acetate extract at 200 g/mL concentration showed similar activity to aspirin at the same concentration. The activity of this extract increased with increasing concentration of the extract. Six compounds were reported to be isolated from this type of extract. Dillapiol and its derivative 6-allyl-5-methoxy-1,3-benzodioxol-4-ol are predicted to be compounds that have anti-inflammatory effects by inhibiting the membrane permeability mechanism of ethyl acetate extract. Ethyl acetate extract showed the best anti-inflammatory activity among the other type of extract from sirih bumi. Ethyl acetate extract is a type of extract with the best anti-inflammatory activity from sirih bumi.